2013
DOI: 10.2151/sola.2013-027
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions for Tropical Cyclogenesis Associated with African Easterly Waves

Abstract: The factors of tropical cyclone (TC) genesis that are associated with African easterly waves (AEWs) were analyzed. We detected AEWs that passed over the West African coast (WAC) using ERA-interim data from July to September 2000−2010 and examine differences between the characteristics of AEWs that either develop or do not develop TCs. We first examined the environmental conditions of the AEWs that develop TCs and their dependencies on genesis location. We found that the mid-level relative humidity near the WAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…When AEW activity is estimated using eddy kinetic energy (EKE), a correlation with Atlantic TC genesis is apparent in the lower troposphere, especially during weak to moderate EKE years, but is weak in the midtroposphere (Russell et al, ). The lack of a clear interannual relationship between AEWs and TCs may be in part because the Atlantic basin receives an abundance of AEWs each hurricane season, with only about 15–20% of AEWs developing into TCs (Agudelo et al, ; Dunkerton et al, ; Frank, ; Satoh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…When AEW activity is estimated using eddy kinetic energy (EKE), a correlation with Atlantic TC genesis is apparent in the lower troposphere, especially during weak to moderate EKE years, but is weak in the midtroposphere (Russell et al, ). The lack of a clear interannual relationship between AEWs and TCs may be in part because the Atlantic basin receives an abundance of AEWs each hurricane season, with only about 15–20% of AEWs developing into TCs (Agudelo et al, ; Dunkerton et al, ; Frank, ; Satoh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results are synergistic-not in contrast to-previous studies that explore the latter constraints on TC genesis, which have been shown to be climate dependent (e.g., nonstationarity of the SST threshold for genesis) [Vecchi and Soden, 2007]. However, many previous studies [e.g., Ross et al, 2012] have found that the linear relationship between AEWs and Atlantic TCs do not always hold, and whether AEWs will develop into TCs or not depend on many other conditions such as their characteristics [Agudelo et al, 2011] and/or large-scale environment conditions [Peng et al, 2012;Daloz et al, 2012;Satoh et al, 2013;Leppert et al, 2013;Brammer and Thorncroft, 2015;Asaadi et al, 2016], and how they interact with other waves [Ventrice et al, 2011]. This is a caveat that one needs to bear in mind when interpreting our results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The GPI considers 850-hPa absolute vorticity, 600-hPa relative humidity, maximum potential intensity (Bister and Emanuel 2002), and 200-850-hPa vertical wind shear. The GPI is regarded as a parameter to represent how favorable an environment is to TC formation, and has been used to diagnose environmental conditions on TC formation for climate and seasonal scales (Camargo et al 2007a,b;Bruyère et al 2012;Zhao et al 2015) and for synoptic scales (Satoh et al 2013;Yoshida and Ishikawa 2013). In this study, the GPI is calculated at each grid point around the location of TCC formation for every clustering sample.…”
Section: Environmental Conditions Of Tcc Formationsmentioning
confidence: 99%